Synergistic effect and mechanism of meropenem with ciprofloxacin against carbapenem-resistant Acinetobacter baumannii - Feng, Ying; Chen, Xu; Sun, Yu; Guo, Tingting; Wu, Feng; Jin, Feng; Zhou, Jun (Frontiers in Pharmacology, 2025)
IntroductionAcinetobacter baumannii has been recognized as a major public health concern, and carbapenems have been considered the first-line treatment for Acinetobacter baumannii infections. However, their widespread and prolonged use has led to the emergence of carbapenem-resistant Acinetobacter baumannii (CRAB), which has become a significant nosocomial pathogen. The control and treatment of CRAB infections have become a global challenge.MethodsLogistic regression was applied to investigate the clinical characteristics and prognostic risk factors of CRAB infections. Multilocus sequence typing (MLST) of three clinical CRAB isolates was carried out to determine their genotype. The antibacterial efficacy of meropenem combined with ciprofloxacin was evaluated using checkerboard and growth curve assays. Transcriptomics analysis was futher used to analysis the molecular mechanism related to the combination treatment.ResultsLogistic regression analysis identified the duration of antibiotic use, glucocorticoid application, C-reactive protein levels, and creatine kinase-MB levels as independent risk factors for poor prognosis in CRAB patients. Multilocus sequence typing of three CRAB isolates revealed that all isolates were ST208 genotype. Checkerboard and Growth Curve assays demonstrated that the combination of ciprofloxacin and meropenem had significant bactericidal effects on CRAB, outer membrane permeability, membrane potential, and reactive oxygen species generation. Transcriptomic analysis revealed that the combination inhibited efflux pump function, reduced iron uptake, and impacted metabolic pathways, membrane protein synthesis, and stress responses, thereby enhancing bacterial killing.DiscussionThe findings from this study underscore the synergistic effect of ciprofloxacin and meropenem not only offers a potential alternative treatment strategy but also highlights the importance of combination therapy in overcoming antibiotic resistance, which pose a significant threat to public health.